Colonialidad, género, corporalidades: el Colectivo Gordes Activistas de Argentina (Miscelánea) - Espínola, María Rocío (2025)
This paper examines the case of the Colectivo Gordes Activistas de Argentina (CGA), exploring the concepts of coloniality, gender, and corporeality to examine activism from a specific situational framework. The qualitative approach includes two main strategies: the systematization and analysis of social media content from a socio-semiotic perspective, and the examination of activists’ actions using ethnographic strategies within an interpretive paradigm. This study is framed by theories of mediatization and social discourse circulation, alongside feminist and decolonial critical epistemologies. The objectives are to explore how the CGA critiques body control mechanisms, fat pathologization, and visibility regimes within a sociohistorical context marked by fatphobia and the marginalization of body diversity. The findings underscore how the CGA leverages platforms like Instagram to promote their rights demands and create spaces of resistance and visibility both digitally and territorially. In conclusion, the CGA promotes the “depathologization” and resignification of fat bodies as territories of struggle in the Global South, distinguishing itself from activism in other regions and challenging structures of stigma and exclusion that affect non-hegemonic bodies.